COMPARAÇÃO DE MÉTODOS DE CUBAGEM DE ÁRVORES DO PLANTIO DE EUCALIPTO NA FAZENDA EXPERIMENTAL DA UEMS/AQUIDAUANA - Flores, Priscila Morel; Urbano, Edilson; Paiva, Bruno; Arima, Gilcelene Medeiros; Romeiro, Édpo Makoto (ANAIS DO ENIC, 2014)